DeFreitas, Susan (ed.). Dispatches From Anarres: Tales in Tribute to Ursula K. Le Guin. Forest Avenue Press, 2021 - Francisca Peixoto da Costa Neto (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Review of DeFreitas, Susan (ed.). Dispatches From Anarres: Tales in Tribute to Ursula K. Le Guin. Forest Avenue Press, 2021